New Sesterterpene Diolyl Butanoate from Rice Straw of Oryza sativa - Yang, Ye-Seul; Chung, Ill-Min; Kim, Seung-Hyun; Ahmad, Ateeque (Asian Journal of Chemistry, 2014)
One new compound 2,6,10,14-tetramethyl-18-butanecarboxymethylene-henecos-12-en-17b-ol (1) has been isolated for the first time from the ethyl acetate extract of Oryza sativa of rice straw. The structure of new compound was elucidated with the help of 600 MHz NMR using 1D and 2D spectral methods viz: 1H and 13C aided by ESI/MS and HR-ESI/FTMS and IR spectroscopy.